Prevalence of Early Childhood Caries in 3- to 6-Year-Old Children in Serbia: A National Pathfinder Study - Tamara Peric; Evgenija Markovic; Jovan Markovic; Bojan Petrovic; Biljana Kilibarda; Ana Vukovic; Dejan Markovic (Children)
This study aimed to assess dental caries status of 3- to 6-year-old preschool children in the Republic of Serbia. Stratified cluster sampling was implemented. Children were examined in four administrative regions of Serbia. Dental caries indices (decayed, missing, and filled) for deciduous teeth and the first permanent molar were recorded at the tooth level (dmft, DMFT) and surface level (dfs, DFS). In addition to cavitated caries lesions (ICDAS 3-6), visual changes in enamel (ICDAS 1-2) were recorded. This study included 1060 3-year-old and 1820 6-year-old children in Serbia. Fifty-six percent of 3-year-olds and 21% of 6-year-olds were caries-free. The mean dmft was 2.11 ± 3.45 for 3-year-olds and 4.46 ± 3.69 for 6-year-olds. The mean dfs was 2.62 ± 5.56 for 3-year-olds and 6.06 ± 6.33 for 6-year-olds. The decayed component was dominant in dmft/dfs. The prevalence of surfaces with initial lesion was 8% for 3-year-olds and 13% for 6-year-olds. Among children diagnosed with early childhood caries, 54% of 3-year-olds and 37% of 6-year-olds had a severe form. The mean DMFT was 0.15 ± 0.55, with only the first permanent molars being affected. Dental caries remains a significant public dental health issue among preschool children in Serbia. There is a noticeable trend of increasing numbers of decayed teeth as children progress through their preschool years. It is imperative to take corrective action enhance the existing oral health prevention program in Serbia with the aim of achieving better dental health among preschool children.